Perspectives on divine action: reflections on the theological legitimacy of approaches to divine action in the V.O./C.T.N.S. series “scientific perspectives on divine action.” - Cross, S (2017)
This thesis critically appraises the theological legitimacy of theories of divine action (TDAs) posited by four principal contributors to the VO/CTNS series "Scientific Perspectives on Divine Action." Wesley Wildman is chosen for his staunch apophaticism; Robert Russell because of his appeal to objective and noninterventionist divine action and his ontology of quantum indeterminism; John Polkinghorne because of his reliance on kenotic theology to underpin free-process theodicy and his ontology of chaotic systems; and William Stoeger for his interpretation of primary/secondary cause. This engagement broadly matches what Philip Clayton, in the series' final volume, labels an "evangelical-theist or orthodoxtheist" (e-t/o-t) theological perspective. This is a perspective Clayton argues the project otherwise lacks. The thesis proposes that, from this (e-t/o-t) perspective, each of these individuals' contributions to the series proves theologically difficult in some degree. It argues that Wildman's apophatic rejection of Revelation and personal analogy and his reliance on the anthropology of the Modern Secular Interpretation of Humanity (MSIH) is too stark and, ultimately, too anthropocentric. Russell's theory of noninterventionist objective special divine action (NIODA) is theologically difficult in the context of creatio ex nihilo, because it rests on the problematic distinction between 'general' and 'special' divine action (GDA/SDA), and a problematic ontology of quantum indeterminism. John Polkinghorne might be expected to provide the kind of theological perspective Clayton says is absent, but aspects of his approach rest on a theologically problematic interpretation of kenosis and a ‘free-process’ analogy that entails a developmentalist and process-theological metaphysical interpretation of evil. This thesis determines that conflicts at the heart of the VO/CTNS series' debate revolve around two primary tensions. The first tension concerns the scope of 'methodological-naturalism'. The second tension concerns the philosophical nature of 'cause'. Mapping the linguistic, historical, philosophical, and sociological background influences that impact all theological perspectives in the VO/CTNS series at an intentionally broad scale provides the deep context needed to establish not only “how?” but also "why?" these tensions culminated in the series' marginalisation of the traditional (e-t/o-t) perspective on divine action. The thesis therefore concludes that Clayton is correct to assert that the (e-t/o-t) theological perspective is missing from the VO/CTNS series. The thesis also concludes, however, that when these tensions are adequately contextualised, that marginalisation proves philosophically unnecessary as well as theologically undesirable and that Clayton's own demand for theological “traction” through scientific constraint is too metaphysically restrictive. Methodological-naturalism prohibits, at least in practice, a 'theology of nature', permitting only a ‘natural theology’ in some key respects. This much broader background context also allows us to recognise the influences of what Charles Taylor calls "cross pressures" that have driven secularisation. These tensions clash conspicuously in the "problem of evil" which cannot be bracketed off from the task of theological reflection on the series. Contextualising these tensions in relation to both 'evil' and the VO/CTNS series' methodological ambitions, highlights the significance of sociological as well as rational influences on individual choices of theological perspective. The meaning of 'cause' and the scope of methodological-naturalism together form a philosophical and theological locus for the series. Closer investigation of this locus reveals that Russell's and Polkinghorne's contributions to the VO/CTNS series suggest a univocal interpretation of 'cause' and 'freedom' that departs from both the "two languages" perspective of Stoeger’s Catholicism and Protestant neo-Orthodoxy. This, raises the important question whether some perspectives in the series represent what, by Nancey Murphy's criteria, represents an ipso facto change of theological tradition. A change that marks an important distinction between Russell's and Polkinghorne's perspective on divine action and the (e-t/o-t) theological perspective that Polkinghorne, especially, might be thought by some to have represented. Having demonstrated that Clayton is, in fact, correct to argue that the (e-t/o-t) theological perspective is indeed missing in the VO/CTNS series, the thesis seeks a more overtly theological perspective on divine action by engaging positively with Vernon White. In view of the various demands for any theologically adequate (e-t/o-t) TDA; now more fully clarified in the broad perspective provided by earlier chapters; it finds White's TDA of universal special divine action (USDA) theologically credible and convincing. That is because White's perspective embodies the three elements that this thesis concludes are vital for any adequate theological perspective on divine action: the need to mind three kinds of gap; the ontological gap between immanent creation and the transcendent Creator; the immanent gap between methodologicalnatural 'data' and the full gamut of human experience; and, finally, the gaps that exist, as Rowan Williams so evocatively phrases things, at "the edge of words". Discussion of divine action demands a careful accounting of the way we use language. Neither univocal nor equivocal speech can disclose divine action "well". What is required instead, is careful and painstaking attention to the work we are asking words to perform in representing divine action truthfully. Attention to the meaning of words like 'model', 'cause', 'methodological-natural', and 'freedom'. The thesis concludes that, with these three elements in place and correctly aligned, the strengths and weaknesses of the VO/CTNS series come more clearly into view and that, far from signalling a "crisis" for contemporary theology, this broader context shows the route to a credible TDA from the (e-t/o-t) perspective, if navigated with proper methodological care, remains navigable for anyone wishing, still, to travel that way. Chapter Outline Since we cannot map what cannot be recognised or represented, chapter 1 queries the role of language per se for representing, truthfully, Divinity and transcendence. Tensions prove to be inherent to the way we use words, and their capacity to intimate transcendence is illustrated by juxtaposing Rowan Williams' exploration of "the edge of words" with Nicholas Saunders bleak assessment that the VO/CTNS signifies a "crisis" for contemporary theology. This chapter suggests why Saunders may have been driven to such a bold, if negative, viewpoint, concluding that, however unavoidably provisional and partial language remains, it is metaphysically possible to ground the claim that speech about God can be truthful. It then tentatively explores how best to frame that speech, investigating the role of certain tropes and a tension that resides in the semantic fluidity of "critical-realism". This flexibility means that the apparently univocal use of the word 'model' may mask differing epistemologies of the word for the scientist and the theologian. The ambiguity in the relationship between model and metaphor is then employed to evaluate the role that "causal joint" plays in framing the science-theology debate over divine action. Potential limitations in the appeal to "joint" provide an impetus for illustrating how the dialogue on divine action might be well served by a renewed analysis of the role its dominant tropes play, in view of their sociological influences; emphasising also the value of deploying a plurality of epistemic sources for framing dialogue about divine action. Chapter 2 presses the conclusion that we can speak truthfully about God to ask "How, then, shall we do so?" The multi-levelled methodological demands of biblical hermeneutics are therefore outlined. Tensions between immanence and transcendence generate a range of choices at three hermeneutical levels: exegetical, systematic, and philosophical. The consequences of differing choices are illustrated in the divergent hermeneutical stances of Wildman, Russell, Polkinghorne, alongside Ian Barbour and Arthur Peacocke. Deeper context is then provided by, in turn, plotting these approaches in relation to major theological trends: Bultmann's demythologisation; the Biblical Theology movement; Open theism; and kenotic theology and philosophy in the late twentieth century. Yet chapter one has shown why fully demythologised TDAs are inadequate to the transcendent 'data' the (e-t/o-t) perspective reflects. Consequently, the remythologising approach of Vanhoozer is introduced to exemplify a richer, theologically adequate, biblical hermeneutic from this (e-t/o-t) perspective. Chapter 3 Applies the same methodological question to science, exploring the limits of methodological-naturalism. In the VO/CTNS series, tensions between transcendence and immanence coalesce around a debate over the meaning, and scope, of divine "cause". This tension is charted by evaluating how Wildman, Russell and Polkinghorne answer the question of whether God needs "gaps" in which to act. I pick up questions and concerns about the meaning of 'action', identified in the two previous chapters, to argue that the boundary between methodological-naturalism and metaphysical speculation is poorly defined in the VO/CTNS series. I then draw on the speech-act work of Nicholas Wolterstorff to demonstrate that efficient causation alone cannot exhaust the meaning of 'cause' when considering potential TDAs, illustrating thereby why Gregory Dawes, in his investigation of methodological-naturalism, is right to conclude that science cannot rule out divine action in principle. This shows a need to reconnect 'cause' with transcendence. But this in turn raises a problem with methodological-naturalism. The thesis therefore engages with Dawes's defence of the "adequacy" of methodological-naturalism, arguing that Dawes's dismissal of revelation as a truthful source of epistemology may be irrational, and that his recognition that methodological-naturalism cannot rule out divine action in principle is a correct, and important, conclusion. The problem of evil is a major background concern for many contributors to the VO/CTNS series and, though this presents something of an organisational difficulty, it renders the topic too important to bracket off or defer further. Yet evil is easily exacerbated if treated simply in abstract, intellectual terms. Consequently, chapter 4's discussion is framed around an immanent test case: the crash of an Air France Concorde in July 2000. This chapter charts three main theological perspectives on evil; apophaticism of the kind Wildman postulates; the Augustinian approach by which evil is a contingent consequence of an angelic and human "Fall"; and an Irenaean developmental theodicy in which evil and suffering are necessary consequences of the kind of freedom creation demands to be fully as God intends. The accident provides a test case for evaluating how the apophaticism of Wildman and the free-process defense of Polkinghorne (the latter almost universally endorsed by contributors to PNE) cash out. The role of Revelation and Tradition, particularly in light of Vanhoozer’s programmatic remythologisation of biblical language in chapter 2, is then brought into service in potential partnership with Russell's idea of creative mutual interaction (CMI), to reject a thoroughly demythologised doctrine of the Fall in pursuit of scientific 'traction', and to call, instead, for a remythologisation that adequately maintains the core doctrinal relation between agential and natural evil represented by Revelation and Tradition. It is acknowledged that this (e-t/o-t) theological perspective is a minority interpretation of that doctrine in both the VO/CTNS series and the broader science-theology dialogue about natural evil at present. In each chapter thus far, an unavoidable, deeper, background tension between immanence and transcendence has motivated disparate theological perspectives. In chapter 5 this tension is brought squarely into the foreground to evaluate both its provenance and its form. Drawing on recent sociological theories of secularisation and its effects on theories of epistemology, detailed by Charles Taylor and Peter Harrison, the thesis plots the theological approaches of Wildman, Russell and Polkinghorne, allowing it to pick up several themes from earlier chapters, especially the nature and scope of freedom and causation. This deeper background serves to highlight historical and sociological factors shaping individual and communal preferences for particular TDAs, and for relating science to theology. Ultimately, the thesis finds strong grounds for challenging Philip Clayton’s insistence that any theologically adequate TDA must entail certain forms of 'traction' with the scientific perspective. Charting these large-scale and broader background "unthought" influences on the VO/CTNS series allows this thesis to tackle more fully the unresolved but more fine-grained question of whether (and "why?") Clayton is right that the (e-t/o-t) perspective is unrepresented in the series. The answer entails remapping the centre of VO/CTNS debate – the meanings of "cause" and "freedom" - at a more precise scale. Chapter 6 achieves this by comparing Stoeger’s Catholic theological perspective with Polkinghorne's Anglican evangelical perspective and Russell's Protestant approach, again highlighting the importance of metaphysical commitments to our faith claims. But, drawing on Philip Jacobs's analysis of the VO/CTNS series, I then show how both Polkinghorne and Russell differ not only from Stoeger’s more Catholic perspective, but also from the (e-t/o-t) perspective; in subtle, but significant ways. Jacobs's analysis, taken together with this thesis's findings, supports Clayton's claim that the (e-t/o-t) perspective is indeed absent from contributions to the VO/CTNS series. Ultimately then, there is no doubt the (e-t/o-t) perspective is missing from the VO/CTNS series. How though to remedy this, and to what benefit? Chapter 7 begins by recapitulating the core demands of an (e-t/o-t) TDA, and why it is that Wildman's, Russell's, Polkinghorne's, and Stoeger’s approaches all fall short in some area. To remedy this, Vernon White's important, but, in the author's view, under-appreciated contribution to discussion of divine action in The Fall of the Sparrow, and his more recent writings are jointly evaluated to show how his TDA of 'universal special divine action' (USDA) better meets the theological demands of an (e-t/o-t) TDA. Having sought to rehabilitate White's theory of USDA, the thesis turns briefly to consider some general principles for framing future discussion of divine action, highlighting three principles or key ingredients for fruitful future dialogue. The first is a demand to pay careful attention to the ontological gap between the Creator and His creation. This gap has operative consequences for the limits of human ration and human epistemology and this thesis observes that reducing or "constraining" divine ontology in view of human epistemology appears to be a recurring temptation to those seeking to describe divine action. Secondly, there is a need to pay equally careful attention to the epistemological gap between what methodological-natural science can tell us about the creation and alternative sources of human epistemology, including divine self-revelation, biblical narrative, and the full gamut of human capacities for representing truth, including the turn to literature. This naturally combines with the third demand: more careful attention to what Rowan Williams evocatively calls the "edge of words." There are neither "two languages" nor a single meta-language of divine action. There is only one language, albeit one where words can add up to more than the sum of their parts. This thesis reaches the following conclusion: that we speak about divine action "well" by preserving paradox and recognising the pressure we place on the words we use. This capacity of language rules out both univocity and a strict "two languages" perspective. Nicholas Saunders's depiction of the VO/CTNS series as engendering a crisis for contemporary theology is therefore overdrawn. His conclusion conflates methodological-naturalism and metaphysical naturalism - eliminating transcendence. It misses the metaphysical implications of methodologicalnaturalism; and the work that words describing divine action are being asked to perform. Ultimately, I conclude that while an (e-t/o-t) TDA, in common with all TDAs, faces the difficult and demanding need to connect scientific theorising with philosophy and theology, the route to a credible TDA from the (e-t/o-t) perspective has been falsely marginalised. If navigated with careful attention to the demands and hazards along the route, it remains entirely navigable.